Bio-cronostratigrafia a foraminiferi planctonici della Pietra Leccese (Miocene) nell’area tipo di Cursi-Melpignano (Lecce. Puglia) - FORESI, L. M.; MARGIOTTA, S.; SALVATORINI, G. (2002)
This paper is a further contribution to the micropaleontological-stratigraphical studies on the Pietra leccese, a peculiar Miocene formation of the Salento Peninsula. The planktonic foraminiferal assemblages have been studied from seven sections, sampled in the quarries between Cursi and Melpignano (near Maglie, Lecce). This zone together with that of Lecce have been historically regarded as the type area of the Pietra leccese. A modern scheme have been used to the bio-chronostratigraphical setting of the Pietra leccese. So, the formation has been established to range from the Globigerinoides trilobus Zone to Globorotalia conomiozea Zone and, therefore, from the upper Burdigalian to the lower Messinian. The formation has a thickness of few tens of meters, despite its wide stratigraphical extension and the detrital facies. This small thickness is due to at least three sedimentary gaps: the first (1.8 My at least) is located between the typical Pietra leccese (G. trilobus Zone, upper Burdigalian) and the lightly glauconithic one (Orbulina suturalis Subzone? – O. universa Subzone, upper Langhian); the second (2.5 My at least) is present between the lightly glauconitic facies and the first very fossiliferous level (labelled as “linea a cozze” by the local quarrymen) at the base of a glauconite-rich interval (Paragloborotalia siakensis Zone, upper Serravallian); the third gap (4 My at least) is located within the glauconite-rich interval and it is in correspondence to a second fossiliferous level (Globorotalia conomiozea Zone, lower pre-evaporitic Messinian). The results deriving from this study confirms the stratigraphic and dynamic framework of the Salento Peninsula. Also in other area of the Salento, the Pietra leccese spans the Burdigalian-Messinian time interval and exhibits some sedimentary hiatuses. These hiatuses might be due to erosive/dispersive currents which affected the depositional basin and that varied in intensity in space and time.